Transitions and crossover phenomena in fully frustrated XY systems - Hasenbusch, Martin; Pelissetto, Andrea; Vicari, Ettore (Physical review. B, Condensed matter and materials physics, 2005)
We study the two-dimensional fully frustrated XY (FFXY) model and two related models, a discretization of the Landau-Ginzburg-Wilson Hamiltonian for the critical modes of the FFXY model and a coupled Ising-XY model, by means of Monte Carlo simulations on square lattices L2, L≲103. We show that their phase diagram is characterized by two very close chiral and spin transitions, at Tch>Tsp respectively, of the Ising and Kosterlitz-Thouless type. At Tch the Ising regime sets in only after a preasymptotic regime, which appears universal to some extent. The approach is nonmonotonic for most observables, with a wide region controlled by an effective exponent νeff≈0.8.
Gesehen am 05.07.2022